Petrushka for solo piano: complete ballet - Stravinsky, Igor Fiódorovich. 1882-1971 (Dover classical music for keyboard, 2006)
Containing all of the music from the original 1911 version, this edition presents Stravinsky´s popular ballet in a reduction for solo piano. Suitable for rehearsal or performance, this version is ideal for listeners wishing to examine the inner workings of one of the twentieth century´s greatest masterpieces.